Traditional Sporting Games as an emotional induction procedure - Moya-Higueras, Jorge; March-Llanes, Jaume; Prat, Queralt; Muñoz-Arroyave, Verónica; Lavega-Burgués, Pere (Frontiers in Psychology, 2023)
Experimental designs to induct emotional states have frequently used still procedures. However, more naturalistic methods of emotional induction by letting participants move and interact freely with other participants should be considered. Traditional Sporting Games (TSG) have the above-mentioned characteristics. The general aim of this study was to determine whether the different roles which allowed executing ambivalent interactions induced different emotional states in college students. We developed three studies with three paradoxical TSG (Sitting Ball Game, Four Corners Game, and Pitcher's Game). Before beginning to play, all the participants answered the Positive and Negative Affect Schedule (PANAS) in a mood version. After playing, participants were asked to report retrospectively the emotional state they were feeling in each role of the game, responding to the Self-Assessment Manikin, PANAS, and Games and Emotion Scale-II. Statistical analyses were performed by ANOVA, calculating corresponding effect sizes. Consistently, but specifically, in each game, roles still induced less positive and more negative emotions. Regarding the active roles, more positive and less negative emotions were kindled when the role allowed catching other players. On the contrary, when developing an active role that implied an increased likelihood of being caught, more negative and less positive emotions were experienced. We found some significant interaction effects between the moods and the role played before playing. To conclude, TSG could be an adequate procedure to induct emotional states and to study emotional conditions in a naturalistic way, showing ecological validity.